2010
DOI: 10.1111/j.1741-1130.2010.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging in Down Syndrome: Morbidity and Mortality

Abstract: The life expectancy of adults with Down syndrome has increased dramatically over the last 30 years, leading to increasing numbers of adults with Down syndrome now living into middle and old age. Early‐onset dementia of the Alzheimer type is highly prevalent in adults with Down syndrome in the sixth decade, and this has overshadowed other important conditions related to aging among adults with Down syndrome. The authors' aim was to update and summarize current knowledge on these conditions, and examine causes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 98 publications
2
77
0
1
Order By: Relevance
“…In theory, adults with DS should develop Alzheimer's-type dementia from 35 to 40 years onwards. Although the presence of the characteristic lesions is typical of aging in DS, however, epidemiological studies clearly show that not all members of this at-risk population go on to show symptoms of Alzheimer's-type dementia (Bittles et al, 2006;Coppus et al, 2008;Quanhe et al, 2002;Torr et al, 2010). The risk of developing this disease therefore parallels the risk within the general population, but 20-25 years earlier for adults with DS, highlighting the interval between the appearance of the neuropathological signs and the disease's clinical onset (Zigman, 2013;Zigman & Lott, 2007).…”
Section: Normative Aging and Alzheimer's Diseasementioning
confidence: 88%
See 1 more Smart Citation
“…In theory, adults with DS should develop Alzheimer's-type dementia from 35 to 40 years onwards. Although the presence of the characteristic lesions is typical of aging in DS, however, epidemiological studies clearly show that not all members of this at-risk population go on to show symptoms of Alzheimer's-type dementia (Bittles et al, 2006;Coppus et al, 2008;Quanhe et al, 2002;Torr et al, 2010). The risk of developing this disease therefore parallels the risk within the general population, but 20-25 years earlier for adults with DS, highlighting the interval between the appearance of the neuropathological signs and the disease's clinical onset (Zigman, 2013;Zigman & Lott, 2007).…”
Section: Normative Aging and Alzheimer's Diseasementioning
confidence: 88%
“…According to Rasore-Quartino (1999), life expectancy improved consistently across the previous century, rising from 9 years in 1929 to 12 years in 1947, and 52 years in 1970. It has now reached 61.1 years for men and 57.8 years for women (Bittles et al, 2006;Glasson et al, 2003), although we should point out that not all studies have found a sex difference in life expectancy (Coppus et al, 2008;Torr, Strydom, Patti, & Jokinen, 2010). The study conducted by Bittles et al (2006), based on data from 298 death certificates, found that 29.9% of the adults in their sample died after the age of 50 years, with a quarter of these dying between the ages of 57 and 62 years.…”
mentioning
confidence: 93%
“…6,15,33,34 As previously stated, this disorder is associated with substantial comorbidity and mortality, and frequently overshadows the diagnosis of the other disorders of aging. 34 Differential diagnosis requires the exclusion of other causes of cognitive decline such as medical conditions, medication effects, psychiatric disorders, changes in environment/bereavement and abuse 9,14,35 It is also essential to correctly differentiate age-related cognitive decline from early dementia, 9 since cognitive abilities in most people with DS are below the average level even before they develop dementia, 32 and the domains of communication and socialization are markedly affected by age. 36 Thus, a baseline assessment of functioning must be established for future reference and comparison.…”
mentioning
confidence: 97%
“…Previous reviews on ageing people with DS were concerned with the identification of specific medical problems of ageing in DS and the end of life (Danés, 2012), or with the examination of causes of morbidity and mortality in elderly people with DS (Torr et al, 2010). Because of the premature ageing of people with DS, some diseases appear earlier and more frequently than they do in the general population (Jones et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they display health-related problems that do not normally arise in the general population until around 70 years of age (Holland et al, 1998). Several studies have been carried out to assess the health conditions of elderly people with DS: specific medical problems have been delineated (Mantry et al, 2008;Torr et al, 2010;Danés, 2012;McCarron et al, 2014), and so have the main causes of death (Bittles et al, 2006;Englund et al, 2013). Some studies also investigated the quality of life of people with DS and their families (Brown et al, 2001;McCarron et al, 2002;Brown and Brown, 2009;Werner et al, 2009;Furniss et al, 2012), and the influence that social services have on the functional decline of those with DS (Bertoli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%